2022
DOI: 10.17691/stm2022.14.6.05
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathogenetic Significance of Amylase Level and Microtomographic Index of Synovial Fluid in Various Joint Lesions

Abstract: The aim of the investigation was to study the level of amylolytic activity and microtomographic index of synovial fluid density as well as to substantiate their clinical and pathogenetic significance by identifying correlations with the known informative indicators reflecting characteristic features of the pathological process in various joint diseases.Materials and Methods. Samples of synovial fluid from 95 patients with various joint pathologies at the stage of the disease progression characterized by copiou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…These dosage forms have a prolonged bio-soluble base in their composition, the presence of which makes it possible to exclude frequent administration of the drug, while at the same time ensuring its accurate dosing. The use of ocular medicinal films allows for the preservation of the natural protective film of the cornea, which is destroyed with frequent instillations, promotes the regulation of the cellular and fibrous composition of the organizing connective tissue [11,12]. In medical ophthalmology, there is a large list of medications that have different routes of administration (parenteral, local: topical, and locally injected), which can become one of the causes of undesirable effects.…”
Section: Complications In the Organs Of Vision With Irrational Antibi...mentioning
confidence: 99%
“…These dosage forms have a prolonged bio-soluble base in their composition, the presence of which makes it possible to exclude frequent administration of the drug, while at the same time ensuring its accurate dosing. The use of ocular medicinal films allows for the preservation of the natural protective film of the cornea, which is destroyed with frequent instillations, promotes the regulation of the cellular and fibrous composition of the organizing connective tissue [11,12]. In medical ophthalmology, there is a large list of medications that have different routes of administration (parenteral, local: topical, and locally injected), which can become one of the causes of undesirable effects.…”
Section: Complications In the Organs Of Vision With Irrational Antibi...mentioning
confidence: 99%
“…In most patients, the change in the number of lymphocytes was within the range of normal values. In patients with rheumatoid arthritis, a decrease in the concentration of serum Creactive protein was observed as early as 1 week after the start of the use of baricitinib and remained reduced throughout the entire period of use (Alzamora et al, 2020;Schendrigin et al, 2022) .…”
Section: Description and Pharmacological Effect Of The Drugmentioning
confidence: 99%
“…One of the drugs that they decided to use for the treatment of pregnant women with COVID-19 was Baricitinib. Baricitinib is a drug for the treatment of rheumatoid arthritis, the evaluation of its use for the treatment of COVID-19 in pregnant women is discussed further (Taylor et al, 2017;Alzamora et al, 2020;Nana & Nelson-Piercy, 2021;Rasmussen & Jamieson, 2022;Schendrigin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In chondrocytes, ascorbic acid and dihydroascorbate are translocated via sodium-dependent vitamin C transport (SVCT-2) and glucose transport GLUT 1, respectively. In vitro, ascorbate and ascorbic acid stimulated the synthesis of type I and II collagen, proteoglycans, and aggrecans in joint chondrocytes (Schendrigin et al, 2022). An in vivo study in STR/ort mice (which developed osteoarthritis) showed that long-term administration of collagen hydrolyzate can reduce the degenerativeness of cartilage tissue affected by osteoarthritis and delay its development (Rzhepakovsky et al, 2021).…”
Section: Experiments In Cell Culturementioning
confidence: 99%